2022
DOI: 10.1186/s12903-022-02090-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of oral health status in a Ghanaian population: rationale, methods, and population characteristics

Abstract: Background Oral health surveys aid in estimating the oral health of a population and provide a projection for future oral health care needs. We report the procedures and rationale of a survey carried out to assess the oral health status and risk factors for oral disease among adults in the Greater Accra Region (GAR) of Ghana. The objective was to provide prevalence estimates on dental diseases, oral health behaviour and risk factors, and to establish baseline epidemiological data on the populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
1
8
1
Order By: Relevance
“…This fact was clearly reflected in the data of this study, where only 4.4% of the 250 patients with partial or total edentulous teeth who came for an estimate finally underwent a removable prosthesis treatment. These data seemed to be consistent with those provided by [45][46][47].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This fact was clearly reflected in the data of this study, where only 4.4% of the 250 patients with partial or total edentulous teeth who came for an estimate finally underwent a removable prosthesis treatment. These data seemed to be consistent with those provided by [45][46][47].…”
Section: Discussionsupporting
confidence: 89%
“…Other studies focused on the African population [45,48] have indicated the need to improve oral hygiene education and healthy eating. We should bear in mind that the efforts made by the social and health administrations should be joint if we want to have an impact on greater access to social and health care, including oral health care.…”
Section: Discussionmentioning
confidence: 99%
“…Studies done in different countries have also shown this gender difference in caries prevalence, female having a higher prevalence than males. [15][16][17] This could be due to risk factors among women like different salivary composition and flow rate, genetic variations, dietary habits, hormonal effects, psychosocial and economic factors and earlier teeth eruption pattern in females leading to longer exposure of teeth to oral environment. [18][19][20] Extraction was the treatment need among 37.68% of the adults in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The oral health sector in Ghana is experiencing growth, but there is little investment in both private and public practice [13][14][15]. The sector's underdevelopment is evident in the low ratio of dental practitioners to patients, estimated at 1 in 104, 000 [16,17]. The dental sector is further characterized by spatial inequality whereby 75% of dentists operate in urban areas, with an estimated 70% situated in the two largest cities in the country, that is Accra and Kumasi [15,17].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it is important to highlight that about 400 million people in SSA have been affected by oral health issues, thereby receiving a growing attention as a public health concern. This situation may be particularly relevant among older people in Ghana where the prevalence of caries and periodontitis is higher among those aged 55 years or older [16]. To this end, the current study uses a representative survey of adults aged 60 or older from three regions of Ghana to examine the association between unmet dental care needs and household food security status.…”
Section: Introductionmentioning
confidence: 99%